Two-tier image annotation model based on a multi-label classifier and fuzzy-knowledge representation scheme. (April 2016) - Ivasic-Kos, Marina; Pobar, Miran; Ribaric, Slobodan
Abstract: Automatic image annotation involves automatically assigning useful keywords to an unlabelled image. The major goal is to bridge the so-called semantic gap between the available image features and the keywords that people might use to annotate images. Although different people will most likely use different words to annotate the same image, most people can use object or scene labels when searching for images. We propose a two-tier annotation model where the first tier corresponds to object-level and the second tier to scene-level annotation. In the first tier, images are annotated with labels of objects present in them, using multi-label classification methods on low-level features extracted from images. Scene-level annotation is performed in the second tier, using the originally developed inference-based algorithms for annotation refinement and for scene recognition. These algorithms use a fuzzy knowledge representation scheme based on Fuzzy Petri Net, KRFPNs, that is defined to enable reasoning with concepts useful for image annotation. To define the elements of the KRFPNs scheme, novel data-driven algorithms for acquisition of fuzzy knowledge are proposed. The proposed image annotation model is evaluated separately on the first and on the second tier using a dataset of outdoor images. The results outperform the published results obtained on the same image collection, both on the object-level and on scene-level annotation. Different subsets of features composed of dominant colours, image moments, and GIST descriptors, as well as different classification methods (RAKEL, ML-kNN and Naïve Bayes), were tested in the first tier. The results of scene level annotation in the second tier are also compared with a common classification method (Naïve Bayes) and have shown superior performance. The proposed model enables the expanding of image annotation with new concepts regardless of their level of abstraction. Highlights: Multi-label classification and knowledge-based approach to image annotation. The definition of the fuzzy knowledge representation scheme based on FPN. Novel data-driven algorithms for automatic acquisition of fuzzy knowledge. Novel inference based algorithms for annotation refinement and scene recognition. A comparison of inference-based scene classification with an ordinary approach.